Inventivitas Pengrajin Rencong Suevenir dalam Mewujudkan Gampong Wirausaha - Ali, Masri; Machmud, M. Nizar; Iskandar; Akhyar; Husni; Putra, T. Edisah; Thalib, Sulaiman; Ibrahim, Masri (Yayasan Kawanad, 2022)
In Aceh Besar, Suka Makmur and Lam Phueot villages, lotus root souvenir manufacturing faces several obstacles such as inadequate marketing strategies and lack of skill in the process. Therefore, this initiative seeks to provide partners with production-related solutions by integrating technology with Rencong souvenir molds. The implementation team also performs socialization and consulting related to internet marketing of products to increase market access and outreach. Program objectives were achieved using the Participatory Rural Assessment Act (PRA). From this initiative, his Mitra Pak Majid of Rencong Souvenir Crafts was able to provide capital support in the form of a bulk casting business.